Lipomatous Tumors in Pediatric Patients: A Retrospective Analysis of 50 cases - Mine ÖZŞEN; Ulviye YALÇINKAYA; Zeynep YAZICI; Mehmet Bartu SARISÖZEN (Federation of Turkish Pathology Societies, 2020)
Objective: Although lipomatous tumors are the most common type of mesenchymal tumors in adults, they account for less than 10% of all soft tissue lesions in pediatric patients. In this descriptive study, we aim to present our series of pediatric lipomatous tumors consisting of lipoma, neural fibrolipoma, lipoblastoma, atypical lipomatous tumor, myxoid liposarcoma and pleomorphic liposarcoma, and to evaluate the clinicopathological characteristics of these tumors in reference to the literature. Material and Method: In this study, pediatric lipomatous tumor cases diagnosed between 2002 and 2018 were screened from pathological archives and retrospectively evaluated. Results: A total of 50 cases were diagnosed with lipomatous tumor within the mentioned period. Of the total cases, 24 were female (48%) and 26 were male (52%), with age distribution ranging from 1 to 204 months. Histopathological examination revealed lipoma in 26 cases (52%), lipoblastoma in 19 (38%), atypical lipomatous tumor in 2 (4%), myxoid liposarcoma in 2 (4%), and pleomorphic liposarcoma in 1 case (2%). Conclusion: Although lipomatous tumors are the most common type of mesenchymal tumors; they rarely occur in children. Since there is a limited number of studies on pediatric lipomatous tumors in the literature, there is insufficient data on the prevalence and incidence of these tumors. These tumors may slowly enlarge to greater sizes, especially those localized in deep tissues, and may cause various clinical symptoms by compressing surrounding tissues. Local recurrences may occur, even after total excision, and require close monitoring.